Demand for Social Responsibility Information by University Investors. - Buzby, Stephen L.; Falk, Haim (The Accounting Review, 1979)
ABSTRACT: This paper presents the results of a mail questionnaire survey of 500 university chief financial officers. The survey attempted to assess the demand for and importance of nine social items of information to universities as investors. Despite the available literature which suggests a growing demand by universities for external corporate social responsibility reporting, the authors advance the tentative conclusion, based on their analysis of 292 usable returns, that university investors may not be a strong source of demand for information about social responsibility.